L’arrivo di Dioniso ad Argo (Pausania 2.20.4, 22.1, 23.7): narrazione mitica ed elementi di culto - Beatrice Gavazza (Mythos, 2023)
The paper examines the myth of Dionysus’ arrival in Argos reported by Pausanias (2nd century AD) in Periegesis 2.20.4, 22.1 and 23.7 as an aetiology of Argivian monuments (tombs of maenads, sanctuary of Dionysus Krēsios). The prominent role accorded to the citizens’ resistance and the hero Perseus will lead to a political interpretation of the myth (section 1). Convergences between this myth and the cult (with particular attention to the integration issue of external elements into a local community) will be verified through the comparison of Pausanias’ account and historical documents of Dionysian cults (sections 2-3). Finally, the results of the previous analysis will be compared with two Hellenistic fragments by Euphorion of Chalcis (3rd century BC; fr. 19a, 40-44 and fr. 109, 17-26 Lightfoot) and will open up new interpretations of them (section 4).